Microwave-assisted extraction of bioactive compounds from Sarawak Liberica sp. coffee pulp: Statistical optimization and comparison with conventional methods - Ching, Joel Jue Wong; Elexson, Nillian (2023)
Coffea liberica, commonly known as Liberica coffee, is a kind of coffee that originated in Liberia, a West African country. It is considered a less- known coffee bean vari-ety, which accounts for less than 2% of commercially produced coffee worldwide. In this study, the influences of optimization of microwave-assisted extraction (MAE) on the total phenolic content (TPC), total flavonoid content (TFC), and total carbo-hydrate content (TCC) of bioactive compounds extracted from Sarawak Liberica sp. coffee pulp were studied. Response surface methodology was adopted with a face- centered central composite design to generate 34 responses by taking three micro-wave parameters into consideration, microwave power (watt), time of irradiation (second), and solvent-to-feed ratio as independent variables. As a result, the findings revealed that optimum extraction conditions were conducted as follows: microwave power of 700 W, time of irradiation of 180 s, and solvent-to- feed ratio of 86.644:1. While under optimal extraction conditions, MAE outperformed conventional mac-eration extraction in terms of extraction efficiency and had no significant difference (p< .05) with Soxhlet extraction on the extraction of TPC (12.94 ± 2.25 mg GAE/g), TFC (9.84 ± 0.38 mg QE/g), and TCC (876.50 ± 64.15 mg GE/g). Present work advances the usage of Sarawak Liberica sp. coffee for the development of functional products and aids in reducing environmental pollution by utilization of coffee pulp waste.